Comparison of pain threshold, health and functional status of females with fibromyalgia and multiple sclerosis: a pilot study - Ozgocmen, Salih; Kaya, Arzu; Gulkesen, Arif; Bulut, Serpil; Ardicoglu, Ozge (Taylor & Francis Ltd, 2006)
Objectives. Fibromyalgia (FM) and multiple sclerosis (MS) are known to cause disability and have an impact on physical functioning, social functioning, and emotional well-being of affected individuals. The aim of this study was to compare pressure pain threshold, health and functional status in females with FM and MS who were ambulatory. Methods. Control point scores (CPS), total myalgic scores (TMS; using an algometer), tender point (TP) counts, and chronic widespread pain were assessed in females with FM and MS and in healthy age-matched female controls. The Fibromyalgia Impact Questionnaire (FIQ), and the Nottingham Health Profile were performed. The Kurtzke Expanded Disability Status Scale (EDSS) was used to estimate the disability status of persons with MS. Results. Fibromyalgia patients have significantly lower CPS and TMS than MS patients and controls. Multiple sclerosis patients had similar CPS but significantly lower TMS compared to controls. Tender point counts were significantly higher in FM than MS patients and controls. Patients with MS had a higher numbers of TPs with respect to controls. Chronic widespread pain was reported by only three patients with MS and these patients did not meet FM criteria for tender point counts. Fibromyalgia patients had significantly lower FIQ-first item scores than MS patients. FM patients had higher NHP section scores in pain, social isolation, emotional reaction, sleep and energy, but similar physical mobility compared to MS patients. In MS patients energy and physical mobility dimension of NHP and FIQ-first item scores correlated with EDSS (r = 0.42, P = 0.047, r = 0.83, P = 0.001, and r = 0.62, P = 0.001, respectively). Conclusion. This cross-sectional study warrants further research comparing FM and MS, which share a lot of clinical and psychosocial features or may coexist. Chronic pain and related fatigue, social and emotional reactions and disability seem to be important components in FM, so taking care of these components, in other words a biopsychosocial model, may improve disease outcome and quality of life not only in FM but also in MS.
Keywords: pain threshold; multiple sclerosis; fibromyalgia; functional ability; health status